(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article examines the examination of blood samples taken from cows with endometritis, the levels of erythrocytes, leukocytes, monocytes, eosinophils, neutrophils in the blood, and biochemical parameters of blood serum, and provides practical conclusions.